Analisis Pengaruh Kepribadian, Motivasi, dan Lingkungan Sosial Terhadap Minat Berwirausaha (Studi Kasus pada Mahasiswa Program Studi Manajemen Universitas Tidar) - Akhmad Fauzan; Khairul Ikhwan (International Forum of Researchers and Lecturers, 2023)
This research was conducted to examine the influence of personality, motivation and social environment on the interest in entrepreneurship. Case Study of Management Study Program students at Tidar University. This study took a sample of 175 respondents where the data was taken by the questionnaire method. This research is a research with quantitative method, where research data is tested using classical assumption test, multiple linear regression analysis and hypothesis testing using SPSS software. The results showed that there was a positive and significant influence of personality, motivation and social environment together on students' interest in entrepreneurship. Partially, personality and social environment have a positive and significant effect on entrepreneurial interest. However, motivation shows a positive and insignificant effect on interest in entrepreneurship. This research is expected to be a material consideration for the University and also the awareness of students to develop the spirit and interest in entrepreneurship so that it can give birth to many entrepreneurs and contribute to the country's economy.